The "Puck" energetic charged particle detector: Design, heritage, and advancements. Issue 8 (30th August 2016) - Clark, G.; Cohen, I.; Westlake, J. H.; Andrews, G. B.; Brandt, P.; Gold, R. E.; Gkioulidou, M. A.; Hacala, R.; Haggerty, D.; Hill, M. E.; Ho, G. C.; Jaskulek, S. E.; et al.
Abstract: Energetic charged particle detectors characterize a portion of the plasma distribution function that plays critical roles in some physical processes, from carrying the currents in planetary ring currents to weathering the surfaces of planetary objects. For several low‐resource missions in the past, the need was recognized for a low‐resource but highly capable, mass‐species‐discriminating energetic particle sensor that could also obtain angular distributions without motors or mechanical articulation. This need led to the development of a compact Energetic Particle Detector (EPD), known as the "Puck" EPD (short for hockey puck), that is capable of determining the flux, angular distribution, and composition of incident ions between an energy range of 10 keV to several MeV. This sensor makes simultaneous angular measurements of electron fluxes from the tens of keV to about 1 MeV. The same measurements can be extended down to approximately 1 keV/nucleon, with some composition ambiguity. These sensors have a proven flight heritage record that includes missions such as MErcury Surface, Space ENvironment, GEochemistry, and Ranging and New Horizons, with multiple sensors on each of Juno, Van Allen Probes, and Magnetospheric Multiscale. In this review paper we discuss the Puck EPD design, its heritage, unexpected results from these past missions and future advancements. We also discuss high‐voltage anomalies that are thought to be associated with the use of curved foils, which is a new foil manufacturing processes utilized on recent Puck EPD designs. Finally, we discuss the important role Puck EPDs can potentially play in upcoming missions. Key Points: Review of the compact Energetic Particle Detector known as the Puck Puck EPD heritage includes five successful scientific missions Unexpected results and potential advancements of the Puck are discussed